2011
DOI: 10.1115/1.4005289
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Simplification for Thermal Mechanical Analysis of High Density Chip-to-Substrate Connections

Abstract: Finite element modeling (FEM) is an important component in the design of reliable chip-to-substrate connections. However, FEM can quickly become complex as the number of input/output connections increases. Three-dimensional (3D) chip-substrate models are usually simplified where only portions of the chip-substrate structure is considered in order to conserve computer resources and time. Chip symmetry is often used to simplify the models from full-chip structures to quarter or octant models. Recently, an even s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The stress distribution was calculated in the copper pillar using the GPD model, as described previously. 18,20 The stress distribution along the length of the pillars and within the first 1 μm of the silicon substrate was evaluated. Figure 8 shows the maximum stress value for the pillar farthest from the center of the chip, which is the one which experienced the highest stress value as a function of misalignment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The stress distribution was calculated in the copper pillar using the GPD model, as described previously. 18,20 The stress distribution along the length of the pillars and within the first 1 μm of the silicon substrate was evaluated. Figure 8 shows the maximum stress value for the pillar farthest from the center of the chip, which is the one which experienced the highest stress value as a function of misalignment.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure followed previous descriptions of this modeling approach. 18,20 Recently, it has been shown that the half-GPD approach has the fewest degrees of freedom and computation time. 18 In the half-GDP model, the full chip contained a 160 × 160 array of pillars.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation